WEB APPLICATION SURVEY PERFORMANCE EVALUATION PT. KALBE MORINAGA INDONESIA - Sudarma, Hantze; Wahjono, Tri Djoko (Bina Nusantara University, 2013)
Research on this case study aims to evaluate the web application survey PT. KalbeMorinaga Indonesia. This case study was done because of some performance issue on theapplication. The problems related to the ability of software to speed data processing and reporting.Research was done on the performance of software and was combined using the gray box, that is,the evaluation of the test and evaluation of the code of the network itself. In addition, it was usedfor testing software for test automation. Automation tests were done as much as several times witha different number of virtual users. Results obtained were analyzed so as to be used as a referencefor the results which pages have problems with performance issues, and were tested by using asolution which then were tested again on that page and comparing the results. The final results ofthe analysis were compared with the results of the first test and then the results of the analysis andrecommendations for improvement can be used by application developers in the future.